Strategi Pemasaran Pony Plop PT. XYZ pada Periode 2022-2024 di Jabodetabek - Citra, Sonia Fergina; Nadila, Karina; Kurnia, Pepey Riawati; Puspita, Anggun Pesona Intan (Research Center and Case Clearing House (RC-CCH) - Sekolah Tinggi Manajemen PPM, 2023)
Nowadays, Many Indonesians are more aware of living a healthy lifestyle. Thus, such conditions opened many opportunities in the food industry, starting with the emergence of healthy catering companies, healthy snacks, and now healthy snacks made especially for toddlers. Providing snacks for toddlers is very important in their development days as their hunger booster and nutritional support supplement. PT. XYZ was founded in 2018 to sell healthy toddler snacks made from fresh ingredients from nearby farmers. Many of their products have become parent’s and toddler’s favorites, yet their Pony Plop product, launched in 2020, has decreased sales despite many awards won. Pony Plop is similar to the meringue (a dessert made from whipped egg white), which is quite unfamiliar to many Indonesians, although it has considerable nutritional value. Their marketing strategy for Pony Plop has not yet gained sufficient awareness, resulting in poor sales. By conducting an internal analysis, SWOT, and portfolio analysis, suitable marketing strategies were chosen for PT. XYZ. Those strategies are: Improve customer loyalty and retention, Build marketing advantage, and Improve differentiation advantage. Implementing these strategies increased awareness and sales of PT.XYZ is to be expected.